2023
DOI: 10.3389/fnagi.2023.1055433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled cannabis high in Δ9-THC or CBD on the aging brain: A translational MRI and behavioral study

Abstract: With the recent legalization of inhaled cannabis for medicinal and recreational use, the elderly represents one of the newest, rapidly growing cohorts of cannabis users. To understand the neurobiological effects of cannabis on the aging brain, 19–20 months old mice were divided into three groups exposed to vaporized cannabis containing ~10% Δ9-THC, ~10% CBD, or placebo for 30 min each day. Voxel based morphometry, diffusion weighted imaging, and resting state functional connectivity data were gathered after 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…Whether the changes we found in adult females would persist following an extended period of abstinence is unknown. Our laboratory extended these studies on chronic cannabis exposure and age-related changes in brain neurobiology to include very old female mice ( Sadaka et al, 2023 ). Again using the same cannabis sample, vaporization procedure and exposure duration, we found no volumetric changes in the brain with the exception of the DA system as discuss below.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whether the changes we found in adult females would persist following an extended period of abstinence is unknown. Our laboratory extended these studies on chronic cannabis exposure and age-related changes in brain neurobiology to include very old female mice ( Sadaka et al, 2023 ). Again using the same cannabis sample, vaporization procedure and exposure duration, we found no volumetric changes in the brain with the exception of the DA system as discuss below.…”
Section: Discussionmentioning
confidence: 99%
“…The present study on adult female mice also found ADC changes in numerous forebrain areas and the olfactory system but only a few changes in the hindbrain. However, in very old female mice there were no significant changes in ADC values with chronic cannabis exposure ( Sadaka et al, 2023 ). Higher or lower values of ADC usually reflect an increase or decrease, respectively, in extracellular water and have been used to follow subtle changes in gray matter microarchitecture with head injury ( Kulkarni et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations